Output control devices : actuators - Tasnim, Rumana; Arshad, Atika; Khan, Sheroz; Ahmed, Musse Mohamud (IIUM Press, 2011)
The wide spreading applications of aclUalon have opened up sevcf1l1 possibililie; in R"Chrdcat areas. The basic difference belWeen scnsor (e.g., thelll1Oll1Cler) and actuator can be simply referred as: sensor is able 10 measure a signal or stimulus obtaining infonnalion from the -real world- whereas aeruatoc itself can generate a signal or stimulus (see Figure 1.1). In Olher word, a transducer ean conven a physical phenomenon into an electric signal while an aeruator can convcn an electric signal 10 a physical phenomcnon